THE INFLUENCE OF ELECTRONIC WORD OF MOUTH (E-WOM) ON TIKTOK'S SOCIAL MEDIA PLATFORM ON STARBUCKS INDONESIA'S PURCHASE INTENTION - Malva Deandra Perkasa Putri; Osa Omar Sharif (SEAN Institute, 2023)
Currently, of the many industries that are experiencing development, the coffee retail industry is one of the many industries that has rapid development. Of the many coffee shops, Starbucks is one of the most well-liked among teenagers in Indonesia. Starbucks Indonesia experienced a decrease in revenue in 2020, therefore important for Starbucks to communicate through social media or Electronic Word of Mouth (e-WOM) to support consumers in receiving quality and credible information related to products in order to increase consumer Purchase Intention. This study was conducted by sending online surveys to 400 respondents using the Google Form. The descriptive and causal analysis method was used in this study with quantitative methods and data collection through questionnaires. Multiple Linear Regression is the method that used for data analysis in this study and SPSS 25 for windows is used to analyze the data. Based on the data’s outcome data analysis that has been obtained, it can be concluded that e-WOM Quality, Quantity, and Credibility have an impact on purchasing intent that is both positive and significant. The study’s findings are anticipated to be used as evaluation data by Starbucks Indonesia in maintaining and improving the company's performance by providing the best service and meeting the needs of its customers